Exploring Learning Approaches of Generation Z Medical Students - Mutyalapati Venkata Ramulu; Amit Kumar Pal; Dyutimoy Datta; Ashish Pundhir (National Journal of Clinical Anatomy)
Background: Medical education in India has adopted Competency-Based Medical Education, which focuses on learner-centered approaches to develop competent healthcare professionals. The knowledge of students’ learning styles helps develop pedagogical strategies. This study aims to find out the preferred learning style of second-year MBBS students using the VARK model. Methodology: A descriptive cross-sectional study was conducted in May 2024 among 68 second-year MBBS students at All India Institute of Medical Sciences, Kalyani. After obtaining ethical approval, the validated VARK Questionnaire (Version 8.01) was administered physically. Students anonymously responded to the questionnaire, which allowed multiple responses. Data were entered into MS Office 2021, Microsoft Corporation, Redmond, Washington, United States and analyzed using descriptive statistics to determine learning style distributions and modal preferences. Results: All respondents filled out the questionnaire. Kinesthetic was the unimodal technique with the highest preference rate (37.71%), followed by auditory (29.24%), then visual (22.69%), and finally read/write (10.33%). Bimodal preferences prevailed with 51%, such as auditory-kinesthetic (38%) and visual-kinesthetic (26%). Trimodal preferences had 9.4%, especially Visual-auditory-kinesthetic (45%). Quad Model preference was observed in only 1.1%. Conclusion: Kinesthetic learning is the most dominant among medical students, whereas multimodal preferences indicate the need for dynamic, experience-based teaching methods. Curriculum designers must incorporate interactive and practice-based strategies to improve academic engagement and performance. Combining diverse teaching approaches could better realize positive outcomes. Such an adaptive and inclusive learning environment helps them prepare as future healthcare professionals.